On death processes and urn models - Kuba, Markus; Panholzer, Alois (Discrete mathematics and theoretical computer science, 2012)
We use death processes and embeddings into continuous time in order to analyze several urn models with a diminishing content. In particular we discuss generalizations of the pill's problem, originally introduced by Knuth and McCarthy, and generalizations of the well known sampling without replacement urn models, and OK Corral urn models.